Generalized Lebesgue Constants and the Convergence of Fourier–Jacobi Series in the Spaces $L_{1,A,B}$ - Motornaya, O. V.; Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
Generalized Lebesgue constants for the Fourier–Jacobi sums and the convergence of Fourier–Jacobi series in the $L_{1,A,B}$ spaces are investigated.